Examination of public perceptions of microbes and microbiomes in the United States reveals insights for science communication. - Katherine Kokkinias; Katherine Pruneski; Kelly Wrighton; Nicole Kelp (PLoS ONE)
Within a changing research and media landscape, misconceptions and misinformation about microorganisms and microbiomes can arise, necessitating improvements in science communication practices through insights in public perceptions of the microbial world. Yet, little is known about public perceptions of microorganisms and microbiomes, making it difficult to develop tailored messaging. Here we perform an inductive thematic analysis with interviews and surveys from thirty adults across the United States to identify key factors to enhance microbial science communication efforts. Together, our results underscore the importance of 1) recognizing the existing and desired future knowledge of an audience, 2) aligning with broader socio-scientific issues that resonate with people in relevant channels using social networks, 3) fostering collaboration between microbiologists, social scientists, and communicators to improve messaging, and 4) appealing to people's values and emotions to establish meaningful connections. This study concludes that non-microbial interests, such as an interest in health and wellness, may lead to acquisition of microbial knowledge and that people want scientists to share microbial messages preferably on platforms like social media. Additionally, we identified confusion about microbial terms and a desire to understand human-centric benefits of microorganisms and microbiomes. We suggest that microbiologists partner with science communicators to develop microbial messaging, capitalizing on connections to non-microbial interests and appealing to people's microbial worldview.